International medical graduates’ experiences of clinical competency assessment in postgraduate and licensing examinations: A scoping review - Helen Hynes; Nora McCarthy; Anél Wiese; Catherine Sweeney; Nitin Gambhir; Tony Foley; Deirdre Bennett (PLoS ONE, 2026)
Background International Medical Graduates (IMGs) represent a substantial proportion of the medical workforce globally and are known to face difficulties in their working lives, including differential attainment in assessment. This scoping review explores existing literature relating to IMGs’ experiences of clinical competency assessments and identifies gaps in current knowledge. Methods Following the Arksey and O’Malley framework for scoping reviews we examined peer-reviewed literature published between 2009 and 2025, without language restrictions. Three independent reviewers contributed to each stage of the process. The British Education Index, the Education Resources Information Center (ERIC), PubMed, Psych Info, Scopus, and Soc Index were searched. Forwards and backwards citation searching and a grey literature search were also performed. Results We identified 44 publications which met the inclusion criteria. These described the experiences of over 7200 IMGs, who had received their primary medical qualifications in 54 named countries, spanning all 6 world regions as defined by the World Health Organisation. Most sources were from the United Kingdom, Australia, and Canada. The review identified three headline categories which summarise the factors that impacted on IMGs’ assessment experiences: internal and personal factors; external and social factors; and institutional and systemic factors. Notable evidence gaps included the impact of age, gender, country of primary medical qualification, years since last in practice, and lower levels of language proficiency on IMGs’ experiences of assessment. Our review reveals the need for further research from a broader range of medical specialties and from a wider geographic spread to improve our understanding of this important topic. Conclusion This scoping review maps the experiences of IMGs in relation to clinical competency assessment and offers useful insights highlighting both positive and negative influences, which could inform future assessment methodologies and support interventions for IMGs. By creating fairer and more supportive assessment pathways, healthcare systems can harness the full potential of IMGs, ensuring their valuable skills and diverse experiences are retained for the benefit of all patients.